Dynamics Analysis of a New Five DOF Hybrid Machine Tool - Wenwen Xu; Ying Mei; Liuyuan He; Zuo Shen (Jixie chuandong)
Based on the analysis of the new five-degree-of-freedom hybrid machine tool mechanism （（3-RPR+R） & UPS） +P， the Jacobian matrix of the velocity of the mechanism is obtained， and the mapping matrix of the centroid velocity of each branch and the generalized velocity of the centroid of the moving platform is obtained. The dynamics model of the new five-degree-of-freedom hybrid machine tool mechanism is established by applying the principle of virtual work. Finally， the theoretical dynamics analysis of machine tool mechanism is verified by using Matlab and ADAMS simulation software， and the results verify the correctness and feasibility of the theoretical analysis.